Tahsin and Tahfizh Learning Methods Implemented in Madrasah Tsanawiyah - Wahyu Satrio Tunggal; Ita Tryas Nur Rochbani (Zabags Qu Publish, 2024)
The purpose of this study is to provide an overview of how Madrasah Tsanawiyah has adopted the Tahsin and Tahfizh learning technique. Using a qualitative descriptive technique, this study employs a qualitative method. Madrasah Tsanawiyah Raudhatul Hasanah Muara Sabak Barat is the study's target. The study's findings show that the Tilawati method is used for Tahsin and Tahfizh learning in Madrasah Tsanawiyah Raudhatul Hasanah, but the Talaqqi method is used for Tahfizh learning. After graduating from madrasah, students who have followed the Tahsin and Tahfizh learning methods are expected to have memorized two juz (juz 29, 30) and read the Quran fluently